Open-label trial on efficacy of artemether/lumefantrine against the uncomplicated Plasmodium falciparum malaria in Metema district, Northwestern Ethiopia - Wudneh F; Assefa A; Nega D; Mohammed H; Solomon H; Kebede T; Woyessa A; Assefa Y; Kebede A; Kassa M (Dove Medical Press, 2016)
Feven Wudneh,1,2 Ashenafi Assefa,3 Desalegn Nega,3 Hussien Mohammed,3 Hiwot Solomon,4 Tadesse Kebede,2 Adugna Woyessa,3 Yibeltal Assefa,3 Amha Kebede,3 Moges Kassa3 1Department of Microbiology, Immunology and Parasitology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, 2Biomedical Department, College of Health Sciences and Medicine, Dilla University, Dilla, 3Malaria and Other Parasitological and Entomological Research Team, Bacterial, Parasitic and Zoonotic Diseases Research Directorate, Ethiopian Public Health Institute, 4Malaria Research Team, Disease Prevention and Control Directorate, Federal Ministry of Health, Addis Ababa, Ethiopia Purpose: Following the increased Plasmodium falciparum resistance to chloroquine and sulfadoxine/pyrimethamine, Ethiopia adopted artemether/lumefantrine (AL) as the first-line treatment for uncomplicated P. falciparum in 2004. According to the recommendation of the World Health Organization, this study was carried out for regular monitoring of the efficacy of AL in treating the uncomplicated P. falciparum malaria in Metema district, Gondar Zone, Northwest Ethiopia.Patients and methods: This is a one-arm prospective 28-day in vivo therapeutic efficacy study among the uncomplicated P. falciparum malaria patients aged 6 months and older. The study was conducted from October 2014 to January 2015, based on the revised World Health Organization protocol of 2009 for surveillance of antimalarial drug therapeutic efficacy study. Standard six-dose regimen of AL was given twice daily for 3 days, and then the treatment outcomes were assessed on days 0, 1, 2, 3, 7, 14, 21, 28, and any other unscheduled day for emergency cases.Results: There were 91 study subjects enrolled in this study, of whom 80 study subjects completed the full follow-up schedules and showed adequate clinical and parasitological responses on day 28, with no major adverse event. Per protocol analysis, the unadjusted cure rate of Coartem® was 98.8% (95% confidence interval: 93.3%–100%) in the study area. Recurrence of one P. falciparum case was detected on day 28, with a late parasitological failure rate of 1.2%. No early treatment failure occurred. Complete parasite and fever clearance was observed on day 3. Gametocyte carriage was 4.4% at enrollment that cleared on day 21. Although the difference is statistically not significant, a slight increase in the level of mean hemoglobin from baseline to day 28 was observed.Conclusion: The study showed high efficacy and tolerability of Coartem® against uncomplicated P. falciparum malaria, suggesting the continuation as a first-line drug in the study district. However, regular monitoring of the therapeutic efficacy of the drug, possibly with plasma drug-level measurement, is critical among the mobile border population. Keywords: artemether/lumefantrine, cure rate, parasite clearance, fever clearance, uncomplicated malaria